The evolution of the European Convention on Human Rights from its inception to the creation of a permanent court of human rights - Bates, Ed. (Oxford : Oxford University Press, 2010)
The European Convention on Human Rights is probably the most effective system of international human rights control created. This book examines the story of the evolution of the convention over its first 50 years & explains how the system grew up & how it came to exert such an important influence on the states which subscribe to it.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Convention for the Protection of Human Rights and Fundamental Freedoms -- (1950); Human rights -- Europe -- History; European Court of Human Rights